The Tension Between Social Conformity and Individual Freedom: a Study of John Arden’s Live like Pigs - Sibgatullah Nazki (International Journal of Global Sustainable Research, 2025)
This study explores the tension between social conformity and individual freedom in John Arden’s Live Like Pigs (1958). The play critiques rigid social structures in post-war Britain. It highlights society’s resistance to those who challenge conventional norms. The purpose of this research is to examine how Arden dramatizes the conflict between authority and personal autonomy. The focus is on the Sawney family. Their nomadic lifestyle and rejection of middle-class values put them at odds with mainstream society. Arden questions whether individuals can exercise true freedom in a system that enforces uniformity. This study uses a close reading of the play’s text. It analyses themes, character interactions, and dramatic techniques. Secondary literature provides context on Arden’s political and theatrical influences. The study examines how dialogue, setting, and staging reflect power struggles between conformity and resistance. The historical and social backdrop of the play is also considered. Post-war housing policies and class divisions shaped these conflicts. The analysis reveals that Arden presents social conformity as both control and exclusion. The Sawneys seek autonomy but face societal pressure and institutional intervention. Their way of life is regulated against their will. The play also critiques absolute freedom. It shows how fragile independence is within a rigid social order. The conclusion highlights Arden’s broader argument. True freedom remains elusive in a society that values stability over individual agency. The play reinforces his critique of post-war social policies. These policies imposed order at the cost of diversity and self-determination